An assessment of the effect of inventory control systems on organisational performance in the mining sector in Zimbabwe - Dumisani Mawonde; Josphat Nyoni; Percy Mabwe; Lillian Kamvumbi (Cogent Business & Management, 2024)
AbstractThis paper aims to assess the effect of inventory control systems on performance of mining firms in Zimbabwe. A systematic literature review was used to review current and relevant scholarly work. The paper used a quantitative survey approach where a survey questionnaire was utilized to collect quantitative primary data from 203 respondents in mining companies. IBM SPSS AMOS version 22 statistical tool was used to conduct Structural Equation Modelling and Confirmatory Factor Analysis. SEM was used to test the formulated hypotheses and CFA was used to determine convergent and discriminant validities of measurement models. The results of this research reveal a positive direct and positive indirect effect of inventory control systems on performance of mining firms in Zimbabwe. Therefore, the research concludes that inventory control systems are used to optimize inventory levels to avoid high inventory ordering and holding costs and stockouts of raw materials and spare parts in mining firms. Thus, mining firms are recommended to use inventory control systems mentioned in this paper to optimize inventories of raw materials and spare parts to improve their performances. This paper also suggests the implementation of modern computerised inventory control systems for effective inventory control in mining firms in Zimbabwe.